Vacancy-driven shear localization in silicon nitride. (1st January 2021) - Karre, Rajamallu; Guo, Dezhou; Song, Shuangxi; Hu, Yixuan; Liu, Yu; Guo, Qiang; Liu, Pan; Wang, Xiaodong; An, Qi; Reddy, Kolan Madhav
Abstract: Vacancies play an essential role on mechanical properties of ceramics, while it is a challenge to reveal the atomistic process of vacancy-driven failure mechanism due to difficulty in characterizing the atomic defects. Here, we used hexagonal silicon nitride as a prototype ceramic and report the shear localization as a main failure mechanism, which is characterized by combining nanoindentation and scanning transmission electron microscopy. It is revealed that the intrinsic point defects in silicon nitride triggers the nanoscale shear bands on the prismatic slip plane when subjected to high stresses. The quantum mechanics simulations ascertained that the shear bands are mediated by nitrogen defects in tetragon sites during the pure shear deformation. Graphical abstract: Image, graphical abstract